Risk assessment of new sequencing information on genetically modified soybean event 305423. (7th August 2017) - ,; Casacuberta, Josep; Nogué, Fabien; Olaru, Irina; Ramon, Matthew; Waigmann, Elisabeth
Abstract: The GMO Panel has previously assessed genetically modified (GM) soybean 305423 as a single event and as part of a two‐event stack, 305423 × 40‐3‐2. These soybean events were found to be as safe as their conventional counterparts and other appropriate comparators with respect to potential effects on human and animal health and the environment. On 23 February 2017, European Commission requested EFSA to analyse new nucleic acid sequencing data and updated bioinformatics data for soybean event 305423 and to indicate whether the previous conclusions of the GMO Panel on the previously assessed GM soybeans remain valid. The new sequencing data indicated a four base pair (bp) difference compared to the sequencing data originally provided: one bp located in the genomic 3′ flanking region, two bp located in a gene silencing cassette and one bp in a partial promoter. These bp reported as differences in the new nucleic acid sequencing data on soybean event 305423 were already present in the original plant material used for the risk assessment. Thus, with the exception of bioinformatics analyses, including an off‐target search with the dsRNA expression cassette, the studies performed for the risk assessment of the single event soybean 305423 and the two‐event stack soybean 305423 × 40‐3‐2 remain valid. The new sequencing data and the bioinformatic analyses performed on the new sequence including the RNAi off‐target search, did not give rise to safety issues. Therefore, EFSA concludes that the original risk assessment of the single soybean event 305423 and the two‐event stack soybean 305423 × 40‐3‐2 remains valid. Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4968/full